Guinness World Records, 2012. Gamer's edition - Glenday, Craig (Guinness World Records, 2012)
A compendium of facts on video games and gamers, containing information about different platforms; records, such as firsts, fastests, highests, and mosts concerning video games; lists of ten games one should play within a variety of genres; and more.